Comparison of Depression Levels in Early and End Preclinical Students at Pelita Harapan University - Budianto, Claresta Janice; Suryadinata, Neneng (Jurnal Kedokteran Meditek, 2025)
Introduction: Mental health is a crucial concern globally and in Indonesia, especially among medical students who face higher rates of depression than the general population due to academic pressure, high expectations, and social stress. Depression can negatively affect academic performance and future careers. Studies show varying results regarding depression levels between early and end preclinical students. Purpose: This study aims to compare the level of depression in early to end preclinical students at Pelita Harapan University and to see whether there is a relationship between gender and social support and the level of depression. Methods: This cross-sectional study was conducted among 333 preclinical students from the Faculty of Medicine, Pelita Harapan University, in January-March 2024. The data was collected using the Beck Depression Inventory-II and the Multidimensional Scale of Perceived Social Support Questionnaire. Data analysis was performed using SPSS version 26 (chi-square statistical test). Results: The study found no statistically significant difference in depression levels between early and end preclinical students (p-value 0.348). There is a relationship between social support and the level of depression in preclinical students of the UPH Medical Faculty, with a (p-value of 0.001). However, no significant relationship was found between gender and the level of depression in preclinical students, with a p-value of 0.093. Conclusion: Conducted outside major metropolitan areas like Jakarta, the study offers insights into how depression manifests in different geographic and socio-economic contexts. The findings can be used as a consideration for making a faculty or university policy to improve mental health management for medical students, ensuring an effective learning process.